Effects of Lycopene Attenuating Injuries in Ischemia and Reperfusion. (7th October 2022) - Wu, Sijia; Guo, Xiajun; Shang, Jia; Li, Yuanyuan; Dong, Wanglin; Peng, Qianwen; Xie, Zhenxing; Chen, Chaoran
Abstract : Tissue and organ ischemia can lead to cell trauma, tissue necrosis, irreversible damage, and death. While intended to reverse ischemia, reperfusion can further aggravate an ischemic injury (ischemia-reperfusion injury, I/R injury) through a range of pathologic processes. An I/R injury to one organ can also harm other organs, leading to systemic multiorgan failure. A type of carotenoid, lycopene, has been shown to treat and prevent many diseases (e.g., rheumatoid arthritis, cancer, diabetes, osteoporosis, male infertility, neurodegenerative diseases, and cardiovascular disease), making it a hot research topic in health care. Some recent researches have suggested that lycopene can evidently ameliorate ischemic and I/R injuries to many organs, but few clinical studies are available. Therefore, it is essential to review the effects of lycopene on ischemic and I/R injuries to different organs, which may help further research into its potential clinical applications.